2021
DOI: 10.1038/s41467-021-21910-0
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase Usp9x regulates PRC2-mediated chromatin reprogramming during mouse development

Abstract: Pluripotent cells of the mammalian embryo undergo extensive chromatin rewiring to prepare for lineage commitment after implantation. Repressive H3K27me3, deposited by Polycomb Repressive Complex 2 (PRC2), is reallocated from large blankets in pre-implantation embryos to mark promoters of developmental genes. The regulation of this global redistribution of H3K27me3 is poorly understood. Here we report a post-translational mechanism that destabilizes PRC2 to constrict H3K27me3 during lineage commitment. Using an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 135 publications
(113 reference statements)
2
6
0
Order By: Relevance
“…USP9X, which is one of the highly conserved members of the largest DUB family, deubiquitinates and stabilizes substrates to participate in the regulation of the substrate-mediated biological functions (Dupont et al, 2009;Jie et al, 2021;Miotto et al, 2018). Recent studies have revealed that Usp9x is a biomarker for stemness, which is required for stem cell self-renewal through regulation of PRC2-mediated chromatin reprogramming via the interaction, deubiquitination and stabilization of PRC2 in mouse embryonic stem (ES) cells (Macrae & Ramalho-Santos, 2021), or maintaining telomere length by inhibiting HIF-1α protein degradation and activating the transcription of TERT which encodes a telomerase reverse transcriptase in breast cancer stem cells (Lu et al, 2021). In the past few years, dozens of substrates for USP9X have been identified in various cells, such as SMURF1 in breast cancer cells (Xie et al, 2013), ZBTB38 in a stable HeLa cell line (Miotto et al, 2018), PTENαin HEK293T cells (Shen et al, 2019), MIB1 in porcine aortic valve interstitial cells (Majumdar et al, 2021), and KDM4C in lung cancer cells (Jie et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP9X, which is one of the highly conserved members of the largest DUB family, deubiquitinates and stabilizes substrates to participate in the regulation of the substrate-mediated biological functions (Dupont et al, 2009;Jie et al, 2021;Miotto et al, 2018). Recent studies have revealed that Usp9x is a biomarker for stemness, which is required for stem cell self-renewal through regulation of PRC2-mediated chromatin reprogramming via the interaction, deubiquitination and stabilization of PRC2 in mouse embryonic stem (ES) cells (Macrae & Ramalho-Santos, 2021), or maintaining telomere length by inhibiting HIF-1α protein degradation and activating the transcription of TERT which encodes a telomerase reverse transcriptase in breast cancer stem cells (Lu et al, 2021). In the past few years, dozens of substrates for USP9X have been identified in various cells, such as SMURF1 in breast cancer cells (Xie et al, 2013), ZBTB38 in a stable HeLa cell line (Miotto et al, 2018), PTENαin HEK293T cells (Shen et al, 2019), MIB1 in porcine aortic valve interstitial cells (Majumdar et al, 2021), and KDM4C in lung cancer cells (Jie et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…USP9X is a multifunctional posttranslational modulator, which is involved in the regulation of various biological processes in multiple cell types, including proliferation and growth of HEK293T cells (Li et al, 2018), survival of B-cell precursor acute lymphoblastic leukemia (Schwartzman et al, 2017), apoptosis of spermatogenic cells (Kishi et al, 2017), autophagy of Huh7 cells (Jia et al, 2020), stemness of ES cells (Macrae & Ramalho-Santos, 2021), heterogeneity and invasive ability (Aqaqe et al, 2019), and radio-resistance of lung cancer cells (Jie et al, 2021). In mouse ovary, Usp9x is enriched in the GCs of primordial and primary follicles, which indicates that Usp9x is related to mammalian folliculogenesis (Sato et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…How can broadly expressed regulators identify and act on cell-specific targets in the genome? Recent studies have shown that the expression of sequence-specific co-factors can drive tissue-specific epigenetic regulation by tethering them to defined genomic locations [77][78][79]. The highly tissue-specific nature of long long ncRNAs may also support this fine-tuned regulation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Gene counts were obtained from the featureCounts function of subread (v1.5.0) with options: -t exon -g gene_id. Raw counts were imported into R, and normalized to ERCCs with edgeR (v3.32.1) as previously described( 19, 30 ). Data were further analyzed using tidyverse v1.3.0 and plotted using ggplot2 v3.3.5.…”
Section: Methodsmentioning
confidence: 99%